A Novel UPLC-PDA Method for the Simultaneous Determination of Lamivudine, Zidovudine and Nevirapine in Bulk and Tablet Dosage Form. Issue 1 (2nd January 2018) - Mondal, Prasenjit; Mahender, Kunta; Padmaja, Bookya
Abstract: This present paper reports about the development of a novel UPLC method for the estimation of Lamivudine (LVD), Zidovudine (ZVD) and Nevirapine (NVP) simultaneously in bulk and tablet dosage form. Excellent chromatographic separation was achieved by isocratic mode with the mixture of methanol and phosphate buffer (PH-5) in the ratio 70:30% v/v as a mobile phase with Waters HPLC system (Aquity 2996 UPLC) and RP C-18 column (100×2.1 mm x 1.8 μm; make: Waters) as a stationary phase. The detection was performed at 260 nm. Retention time of LVD, ZVD and NVP were found 1.76, 2.24 and 3.75 minutes respectively. The detection and quantitation limits were found 0.023 μg/mL and 0.066 μg/mL for LVD. 0.027 μg/mL and 0.092 μg/mL for ZVD and 0.019 μg/mL and 0.066 μg/mL for NVP. The present method was found suitable for the analysis of marketed formulation, where as the % assay were found within 99-100.6% for all three analytes. Hence the present work was found suitable and reliable for the analysis of LVD, ZVD and NVP in bulk and tablet dosage form.